(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Total Quality Management is an integrative management Philosophy aimed at continuously improving theperformance of products, processes and services to chieve and surpass customer expectations. There are many differences in manufacturing and service industries. The purpose of this study is to understand concept of TQMin both industry sectors and to identify the significant differences (if any) in TQM practices in northern India service and manufacturing organisations. For this purpose related literature is collected and classified in to various categories. The literature is deeply studied and the critical factors that influence the TQM success in industry are determined. Based on these factors a questionnaire was prepared which includes two types of questions, variable questions and ranking questions. Thefirst eight questions are related to the company background and demographic data such as no. of employees, sector of business, type of industry, position of the respondent, etc. The variable questions are grouped in to seven factors such as customer focus, continuous improvement, Team work and involvement, Top management commitment and recognition, training and development, communication in company, measurement and feedback. A total of 60 questionnaires were sent to both types of industry. Then questionnaires were collectedback from various industries and the data was managedin a usable format and the t-test is applied on the data with the help of SPSS & MINITAB Software. The result recorded isthat there is no significant difference in the application of TQM in manufacturing & Service industries.